Effects of high-temperature thermal annealing on properties of aligned multi-walled carbon nanotube sheets and their composites. Issue 6 (2nd June 2020) - Huu Nam, Tran; Goto, Ken; Shimamura, Yoshinobu; Inoue, Yoku; Yamamoto, Go; Shirasu, Keiichi; Hashida, Toshiyuki
ABSTRACT: Aligned multi-walled carbon nanotube (MWCNT) sheets were thermally annealed at high temperatures of 1800°C, 2200°C, and 2600°C. Pristine and thermally annealed MWCNT/epoxy composites were fabricated using hot-melt prepreg processing. Effects of thermal annealing on properties of aligned MWCNT sheets and their composites were examined. Transmission electron microscope images and Raman spectra measurements of the aligned MWCNT sheets showed an improvement of the MWCNT nanostructure after high-temperature thermal annealing. High-temperature thermal annealing did not cause the change in microstructural morphologies of the MWCNT sheets. Although the strength of the MWCNT sheets after high-temperature thermal annealing did not improve, their stiffness enhanced significantly. Particularly, high-temperature thermal annealing increased markedly both the tensile strength and elastic modulus of the aligned MWCNT/epoxy composites. The enhancement in the tensile strength and elastic modulus of the composites is mainly attributed to significant improvement of the MWCNT nanostructure by high-temperature thermal annealing. Generally, high-temperature thermal annealing improved the stiffness of the aligned MWCNT sheets and their composites considerably. Graphical Abstract: